Trauma of displacement in V. S. Naipaul's The Mimic Men - Mehni, Masoumeh; Omar, Noritah; Bahar, Ida Baizura (Canadian Center of Science and Education, 2015)
This research considers displacement in Naipaul’s The Mimic Men as a traumatic experience. Taking an interdisciplinary approach to the subject of my study, it explores the historical and psychological dimensions of the displacement in the novel, as well as its literary representations. In the first step, I depicted the displacement as a traumatic experience for the protagonist by the illness which displacement causes Post Traumatic Stress Disorder. In the second step, I suggested two ways the protagonist goes through to remember their trauma. These ways are two different kinds of memory, namely, “acting out” and “working through”. I take “acting out” and “working through” as different but not opposite processes. “Acting out” and “working through” may never be totally separated from each other, and the two may always mark or be implicated in each other. In the third step, I also looked at the impacts of trauma of displacement on the structural and formal components of The Mimic Men.